Creation of Interactive Learning Media Introduction to Basic Phrase Practicum Based on Virtual Reality Technology - Soetopo, Antonius Adi; Muldani H, Yogi; Muslim, Dede Buchori; Suseno, Suseno (International Journal of Social Discussion, 2024)
Interactive Learning Media in the learning process can be in the form of a relationship between humans and computers or software that allows active learning by not only seeing and hearing but also being able to do something. At the beginning of 2020, the world was shocked by the Covid-19 virus which caused people from various fields to work at home or online (online), including in the field of education. The practicum learning process at the Bandung Manufacturing Polytechnic was constrained during the pandemic because it was not fully carried out offline. One of them is the manufacturing process practicum, so an online learning media was created regarding the clamping of workpieces and cutting tools in the basic milling manufacturing process practicum based on virtual reality technology. This virtual reality-based learning media is made with Unity 3D software. The interactive learning media that has been created is installed on the Oculus Quest 2 device. The learning media includes an introduction to milling machines, clamping workpieces and cutting tools. The results of the virtual reality technology-based learning media testing questionnaire to students showed that the average respondent strongly agreed with 58% for the six aspects of assessment and overall effectiveness with a result of 88.34%.